(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
The aim of this study was to find out the relationship of menstruation in suicidal hanging. In the present study, 30 cases of deaths due to suicide by hanging in women in their fertile age group, which were brought for autopsy, were selected. Most of the deaths occurred in the age group of 13-30 years (25 cases; 83%). Among them, 23 (77%) were married and the majority of the women, 27 (90%), were educated. It was found that instances of suicide by hanging were almost equal in both the employed (13; 43%) as well as the unemployed (14; 47%) women. In 21 cases (70%), the main reason for committing suicide was found to be marital unhappiness. Among the 30 cases that were studied, 17 (57%) were in menstruating phase. The findings of this study revealed that there is a significant relationship between suicide by hanging in women and menstruation.